EXPLORING THE LANGUAGE USE IN WHATSAPP AS STUDY PRAGMATICS: - Lestari, Ajeng Puji (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
Pragmatics is one of study linguistic, which was being applied by the particular utterances as the relationship between linguistics form and the users of its form. For the specific study, the writer narrowed a subject of the research by headlining and conducting an observation to the structural classification analysis of conversation and preference structure in WhatsApp emoticon usage, as Yule (1996) had mentioned the types of structural classification in the first part of conversation such as proposal, offering, requesting, and giving assessment along with the second part as the response utterances either preffered or dispreffered that were also occurred in adjacency pair covered in several expressions such as questioning sequence, insertion sequence, thanking expression, and parting expression that had been found in 11 data resources of chatting were also ensured the confirmation of WhatsApp emoticon contextual meaning by distributing the questionnaire to the 36 other users that were accumulated using percentage and described qualitatively into the data analysis. As the result, it had been found considerable responses argued that WhatsApp emoticons are becoming the importance tools as an online facilitator for communication with the primary reason that emoticons can enhance the messages and can help to express emotions or feelings.